Analysis of Legal Protection for Unregistered Bamboo Woven Craft Businesses from a Copyright Perspective - Andrean Darven Justitio; I Nyoman Bagiastra (Westscience Press, 2024)
This research aims to analyze how legal protection is given to bamboo woven craft businesses whose copyrights have not been registered from a copyright perspective. The problem in this research is related to the existence of a violation of rights committed by other parties who carry out acts of imitation or duplication of woven bamboo crafts in terms of motifs, designs and shapes made by the original owner which are duplicated or imitated by irresponsible parties with the aim of traded without the permission or knowledge of the creator, causing losses to the original creator of the woven bamboo craft. The aim of carrying out this research is to analyze the condition of legal protection for the bamboo woven craft business that occurs in Indonesia. The legal research method used is normative legal research which is carried out by identifying and studying statutory regulations related to Copyright in the issue of providing legal protection in the bamboo woven craft business sector. The approach method used is the legal approach (statue approach) in analyzing existing problems, then the data collected and obtained are processed using qualitative methods. The results of the research are then explained descriptively to provide an overview related to the research results obtained, namely that copyright for works of art and crafts whose copyright ownership has not been registered can still receive legal protection, this is because the copyright of a work attaches automatically to a work created by the creator as long as it has met the requirements as an original work and has been expressed in a concrete form, in which case it has been expressed as a work of woven bamboo craft. However, to obtain stronger legal recognition, bamboo woven works that are developed into bamboo woven craft businesses need to register the copyrighted work.